Immune role of the complement component 6 gene and its associated novel miRNA, miR-727, in half-smooth tongue sole (Cynoglossus semilaevis). (October 2021) - Ma, Hui; Chen, Yadong; Yu, Mengjun; Chen, Xuejie; Qi, Longjiang; Wei, Shu; Fan, Qingxin; Xu, Qian; Zhan, Min; Sha, Zhenxia
Abstract: The complement component 6 ( C 6) gene is a component of the membrane attack complex (MAC), which causes rapid lytic destruction of bacteria. MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene stability, including that of immune genes. However, current research on the function of C 6 and its regulation by miRNAs is lacking. In the present study, we identified and characterized C 6 and a novel miRNA, miR-727 (designated CsC 6 and Cse -miR-727, respectively), of the half-smooth tongue sole ( Cynoglossus semilaevis ) that responded to infection with Vibrio anguillarum, a Gram-negative pathogen of marine fish. The full-length cDNA of CsC 6 contained a 256 bp 5′ untranslated region (5′-UTR), a 2820 bp open reading frame (ORF) encoding 939 amino acids, and a 205 bp 3′-UTR. SMART analysis showed that Cs C6 contains typical C6 domains, including three TSP1 domains, one LDLa domain, one MACPF domain, two CCP domains and two FIMAC domains. CsC 6 and Cse -miR-727 are widely expressed in the 13 tissues of half-smooth tongue sole, and their expression in immune tissues is significantly changed after V. anguillarum infection, generally showing an inverse trend. We confirmed that CsC 6 was the target gene of Cse -miR-727 using the dual luciferase reporter assay and that Cse -miR-727 regulated CsC 6 at the protein level using quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting. The hepatic expression levels of not only the MAC components C 7, C 8α, C 8β, C 8γ and C 9 but also the MAPKs, NF-κβ, AP-1, IL1β, IL6 and TNFα, which are involved in many signaling pathways, changed significantly in half-smooth tongue sole following stimulation with the Cse -miR-727 agomir and inhibitor. This evidence suggested that CsC 6 could be mediated by Cse -miR-727 to affect MAC assembly and immune signaling pathways in half-smooth tongue soles. To our best knowledge, this study is the first to investigate the regulatory mechanism and immune response of complement genes mediated by miRNAs in fish. Highlights: Cse -miR-727 and CsC 6 were expressed in response to Vibrio anguillarum infection. Cse -miR-727 silenced CsC 6 posttranscriptionally. Cse -miR-727 regulated terminal complement pathway and other immune pathways via CsC 6.